Development of auditory and palpatory educational media on pregnancy danger signs for visually impaired mothers - Dian Furwasyih; Sunesni Sunesni; Ilham Akerda Edyyul (Universitas Airlangga, 2021)
HIGHLIGHTS1. Pregnancy dangers should be known by any pregnant mothers, including those with visual impairment. 2. Educational media for visually impaired pregnant mothers can be in the form of auditory and palpatory media. 3. Auditory and palpatory media has been researched and developed in this study.4. The auditory and palpatory media increase the knowledge in health education of visually impaired pregnant mothers as they overcoming difficulties the often found. ABSTRACTObjectives: This study was a preliminary study (pilot project) on auditory and palpatory educational media of pregnancy danger signs for blind mothers. With the development of auditory and palpatory educational media, it was hoped that it helps blind mothers to understand pregnancy danger signs.Materials and Methods: The design of the study was a research and development study adapted into two stages, namely the needs analysis and the product design stages.Results: The results of the development of auditory and palpatory educational media included braille-lettered health education media and audio mp4 media which contained material on the danger signs of pregnancy in blind mothers.Conclusion: Auditory and palpatory media can increase the knowledge in health education because of their function to help overcoming many problems of difficulties in understanding and facilitating the reception of information by blind mothers.